Safety Profile of Biportal Endoscopic Spine Surgery Compared to Conventional Microscopic Approach: A Pooled Analysis of 2 Randomized Controlled Trials - Sang-Min Park; Kwang-Sup Song; Dae-Woong Ham; Ho-Joong Kim; Min-Seok Kang; Ki-Han You; Choon Keun Park; Dong-Keun Lee; Jin-Sung Kim; Hong-Jae Lee; Hyun-Jin Park (Neurospine)
Objective To compare the safety profiles of biportal endoscopic spinal surgery (BESS) and microscopic spinal surgery (MSS) for lumbar disc herniation and spinal stenosis by analyzing the associated adverse events. Methods We pooled data from 2 prospective randomized controlled trials involving 220 patients (110 in each group) who underwent single-level lumbar surgery. Participants aged 20–80 years with radiating pain due to lumbar disc herniation or spinal stenosis were included in this study. Adverse events were recorded and analyzed over a 12-month follow-up period. Results The overall adverse event rates were 9.1% (10 of 110) in the BESS group and 17.3% (19 of 110) in the MSS group, which were not statistically significantly different (p=0.133). Notably, wound dehiscence occurred in 8.2% of MSS cases but in none of the BESS cases. Both groups showed similarly low rates of complications, such as dural tears, epidural hematoma, and nerve root injury. The most common adverse event in the BESS group was recurrent disc herniation (2.7%), whereas that in the MSS group was wound dehiscence (8.2%). Conclusion BESS demonstrated a safety profile comparable to that of MSS for the treatment of lumbar disc herniation and spinal stenosis, with a trend towards fewer overall complications. BESS offers particular advantages in terms of reducing wound-related complications. These findings suggest that BESS is a safe alternative to conventional MSS and potentially offers the benefits of a minimally invasive approach without compromising patient safety.